Analysis of Corrosion-Fatigue Damage and Fracture Mechanism of In-Service Bridge Cables/Hangers. (10th February 2021) - Guowen, Yao; Shicong, Yang; Jinquan, Zhang; Yanling, Leng
Abstract : Cables/hangers are important load-bearing components of suspension, cable-stayed, and through-arch bridges. Their reliability throughout their service life directly affects the safety of these bridges. In this study, to provide a reference for the design, maintenance, and inspection of bridge cables/hangers, their damage and failure mechanisms were theoretically analyzed using finite element analysis and corrosion-fatigue simulation tests of steel wires, based on the characteristics of the cable/hanger damage. The finite element analysis showed that a rotation of 0.00113 rad in the lower anchorage area results in a bending stress of 18.8 MPa, indicating that the effect of the bending stress on the steel wires in this area cannot be neglected, as it is a factor contributing to the failure of long cables/hangers. We further used a salt spray chamber to simulate an acid-rain environment. The results showed the following: (1) corrosion-fatigue damage of the cables/hangers occurs under the combined action of a corrosive environment and an alternating stress. This leads to an intensified corrosion damage, reduced ductility, increased brittleness, and eventually, brittle fracturing of the cables/hangers. (2) In the same corrosive environment, the highest degree of specimen corrosion occurred during alternating stress, followed by static stress, and no stress. (3) After corrosion-fatigue damage occurred for a specimen, its breaking stress was about 60% in comparison to the uncorroded specimen. The percentage elongation at the break also decreased; this was about 40% in comparison to the uncorroded specimen, indicating brittle fracturing. (4) The steel wires of the cables/hangers with corrosion-fatigue damage are more prone to brittle fracture if they are exposed to complex spatial stresses.